Inferior Alveolar Nerve Transposition for Placement of Dental Implants - A Narrative Review - Eldagny, Nevan Mohammed M (Archive of Orofacial Data Science, 2025)
AIM: This article is a narrative review of inferior alveolar nerve transposition for the placement of dental implants in severely atrophied mandibles. METHODS: Clinical reports on dental implants from leading scientific journals and comprehensive searches in PUBMED, QUINTESSENZ, and MEDLINE served as the basis for this review, which includes 190 sources from the literature. The relevant topics presented included nerve anatomy, arterial blood supply, innervations of the mandible, mandibular bone atrophy, factors influencing mandibular bone loss, nerve injury, and evaluation of inferior alveolar nerve disturbance. Methods to avoid inferior alveolar nerve injury were discussed, in conjunction with inferior alveolar nerve transposition for implant placement and various surgical techniques. RESULTS: Inferior alveolar nerve repositioning should be performed by a skilled surgeon. Proper diagnosis and presurgery planning are essential to avoid nerve sensory disturbances. This technique can provide the additional bone required for an optimal implant anchorage while reducing the risk of nerve damage. Regeneration of a nerve injury is evidenced by the spontaneous return of normal sensation, depending on the severity of the injury and the nerve involved. Recovery should be monitored using sensory tests to determine the need for micro-reconstructive surgery, with continued monitoring indicated post-surgery. CONCLUSION: Inferior alveolar nerve transposition can be safely and predictably performed with a lower risk to mental nerve sensibility.